The characteristics of Genesis and Evolution of Debris Flow Fans Based on Fixed Point Observation - zhang, Jinshan; she, Xingju (Italian journal of engineering geology and environment, 2011)
The Liziao Gully and Huajiaopo Gully are 2 tributaries of Jiangjia Gully in its middle reaches, a well-known gully for its debris flows of high frequency. The two gullies are extremely similar in features of their drainage basins, including high frequency of debris flows and rapid formulation of debris flow fans. During field studies, process of movement and accumulation of debris flow fan are observed, and sampling and analysis of debris flows with different features are conducted. Terrain of debris flow fans and their longitudinal and transverse profiles are measured prior to and post rainy season each year. By analyzing evolution process, planar features, longitudinal and transverse section, accumulation rate and other parameters of debris fans in the 2 tributary gullies during 2006-2008, following conclusions are obtained: (1) Influenced by geological and lithological features in its drainage basin, Huajiaopo Gully is larger in unit weight and grain size of its debris flow, and its accumulation fan is formulated in Mound-shape. Whereas debris flow in Liziao Gully is smaller in unit weight and grain size, with debris flows moving on the fan and its accumulation is in a linguiform. Further evolution of debris flow fans is finished with Mound-shaped accumulation and channel shifting. (2) In case of accumulation in main channel, debris flow fans in tributary gullies are formed by aggradation and aggradation height is uniformly distributed at upper and lower parts of the fan. (3) Slopes of debris flow fans on both longitudinal and transverse sections are largely determined by fluidic properties of debris flows. The greater the unit weight is, the larger the slope of debris flows on both longitudinal and transverse sections is.